1999
DOI: 10.1161/01.atv.19.12.2993
|View full text |Cite
|
Sign up to set email alerts
|

Both Raloxifene and Estrogen Reduce Major Cardiovascular Risk Factors in Healthy Postmenopausal Women

Abstract: Abstract-Currently raloxifene, a selective estrogen receptor modulator, is being investigated as a potential alternative for postmenopausal hormone replacement to prevent osteoporosis and cardiovascular disease. We compared the 2-year effects of raloxifene on a wide range of cardiovascular risk factors with those of placebo and conjugated equine estrogens (CEEs). Analyses were based on 56 hysterectomized but otherwise healthy postmenopausal women aged 54.8Ϯ3.5 (meanϮSD) years who entered this double-blind stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
72
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 69 publications
13
72
3
Order By: Relevance
“…In the perspective of DHA and AA, raloxifene seems to be the preferable compound in postmenopausal women when weighed against CEE plus MPA. Raloxifene has beneficial effects on bone density and lipids of raloxifene (de Valk-de Roo et al 1999, Johnston et al 2000, Walsh et al 2000, and in the present study increased DHA levels more strongly than AA (when given in a dosage of 150 mg per day), while n-3 HUFA are relatively deficient compared with n-6 HUFA in the dietary pattern in industrialized countries. The lack of effect on DHA and AA in men, combined with the negative effect on HDL-cholesterol and a significant increase in serum prostate specific antigen (PSA) levels (Duschek et al 2004), would lead us not to recommend raloxifene administration in men.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the perspective of DHA and AA, raloxifene seems to be the preferable compound in postmenopausal women when weighed against CEE plus MPA. Raloxifene has beneficial effects on bone density and lipids of raloxifene (de Valk-de Roo et al 1999, Johnston et al 2000, Walsh et al 2000, and in the present study increased DHA levels more strongly than AA (when given in a dosage of 150 mg per day), while n-3 HUFA are relatively deficient compared with n-6 HUFA in the dietary pattern in industrialized countries. The lack of effect on DHA and AA in men, combined with the negative effect on HDL-cholesterol and a significant increase in serum prostate specific antigen (PSA) levels (Duschek et al 2004), would lead us not to recommend raloxifene administration in men.…”
Section: Discussionsupporting
confidence: 57%
“…Linoleic acid is converted into arachidonic acid, and -linolenic acid is converted into eicosapentaenoic acid and docosahexaenoic acid (Sprecher 2000). lowers total and low-density-lipoprotein (LDL) cholesterol (de Valk-de Roo et al 1999, Johnston et al 2000, Walsh et al 2000. Comparing raloxifene, conjugated equine estrogens (CEE) combined with 2·5 mg medroxyprogesterone acetate (MPA), and placebo in healthy early postmenopausal women and healthy elderly men may increase our understanding of their potential effects on the biosynthesis of n-3 and n-6 HUFA.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen replacement therapy and the selective estrogen receptor modulator (SERM) raloxifene lower plasma Hcy (Walsh et al, 2000;Yildirir et al, 2002). Estrogen, but not raloxifene, increases circulating CRP concentration (de Valk-de Roo et al, 1999;Walsh et al, 2000;Yildirir et al, 2002) by increasing hepatic production of CRP (Walsh et al, 2001;Skouby et al, 2002). Both estrogen and raloxifene have been reported to decrease vascular adhesion molecules (Koh et al, 1999;Blum et al, 2000) by binding to estrogen receptors on the vascular endothelium and modulating transcription of these adhesion molecules (Caulin-Glaser et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…No significant alterations associated to raloxifene were detected in F1ϩ2, fibrinopeptide A, and plasminogen activator inhibitor-1 levels. In another study involving more extensive assessment of the hemostatic system, De Valk-de Roo et al (15) also observed a fibrinogen reduction associated with raloxifene use but without significant alter- ations in other coagulation parameters assessed. In relation to fibrinolysis assessment, no significant modifications were detected in any of the parameters considered, in groups which received raloxifene.…”
Section: Discussionmentioning
confidence: 92%